Principal component analysis for yield attributing traits of sunflower (Helianthus annuus L.) genotypes: Principal component analysis for yield attributing traits of sunflower (Helianthus annuus L.) genotypes - R SASIKALA,; P L VISWANATHAN,; S MANONMANI, (Journal of Oilseeds Research, 2020)
In order to evolve the potential heterotic hybrids in sunflower, efforts are on in plant breeding programmes to select promising parental inbreds for various yield related traits. Ninety one sunflower germplasm accessions were evaluated for seven quantitative traits during rabi2018-19 and data were subjected to biometric analysis for correlation and principal component analysis. PCA analysis revealed that, out of 7 PCs, only 3 PCs exhibited more than 1.0 Eigen value and showed 71.45% variability for 91 genotypes. PC1 reported for highest variability in traits like days to 50% flowering and days to maturity. PC3 showed the positive load on yield attributing traits like 100 seed weight and single plant yield. PC1 and PC3 allowed for simultaneous selection of yield related traits.